Sanguijuelas (Hirudinea: Glossiphoniidae) asociadas a Cryphiops caementarius (Decapoda: Palaemonidae) del Río Limarí, Chile - Patricio Tello; Viviane Jerez; Viviana Olmos (Revista de Biología Tropical, 2007)
Sanguijuelas de las dos especies Helobdella duplicata y H. triserialis (ambas Glossiphonidae) parasitan al camarón de río Cryphiops caementarius en río Limarí, Chile. El 47 % de los camarones estaba parasitado por una o ambas especies de hirudíneos. H. triserialis fue encontrada solo en los pleópodos con los mayores valores de prevalencia (42 %), intensidad (2.9) y ámbito (1-11). H. duplicata se encontró solamente en los filamentos branquiales con una prevalencia de 7 % intensidad de 1.7 y un ámbito de 1-4. La longitud total y el sexo del hospedero, explicarían las variaciones de la intensidad y prevalencia de las infecciones. Sin embargo, cuando se considera el sexo del hospedero, la prevalencia solo aumenta con el tamaño de las hembras. Las características morfológicas de las hembras podrían explicar la mayor intensidad de H. triserialis en la base de los pleópodos, algo relacionado a su vez con un mayor desarrollo del abdomen. Leeches (Hirudinea: Glossiphoniidae) associated to Cryphiops caementarius (Decapoda: Palaemonidae) of the Limarí river, Chile. Two leech species were found parasitizing the shrimp Cryphiops caementarius from Limarí river, Chile. These ectoparasites can act as population regulators or development inhibitors in their host; however the biological characteristics of this host-parasite interaction are unknown. We analyze the inter-specific differences of the parasitism and its relation with host size and sex using quantitative descriptors. Abundance, prevalence, intensity and range were estimated with respect to host size and sex. The leeches belong to two species of Glossiphonidae: Helobdella triserialis and H. duplicata. Forty-seven percent of the hosts were parasitized by one or both leech species. H. triserialis was found only in the pleopod of the hosts with the highest prevalence values (42 %), intensity (2.9) and range (1-11). H. duplicata was found only in the branchial filaments with 7 % prevalence, an intensity of 1.7 and a range of 1-4. The host’s total length and sex can explain the variation in leech intensity and infection prevalence. However, when only the host’s sex is considered, prevalence only increased with size in female hosts. Morphological characteristics of the females could explain the greater H. triserialis intensity in the base of the pleopod and would be related to a greater abdomen development. Rev. Biol. Trop. 55 (1): 255-260. Epub 2007 March. 31.